Gross and Biometrical observations on the Testis of Indian Mongrel Dogs (Canis Lupus Familiaris) - Kumar. K; Kannan. T.A; Geetha Ramesh; G. V. Sudhakara Rao; Rengasamy. S; Ravali. K.S; Afsha Khan (Indian Journal of Veterinary Anatomy, 2024)
The present study was undertaken to record the gross and biometrical details of the testes in dogs of pre- pubertal and post-pubertal age groups. For this, testes were collected from 12 healthy dogs and record the various gross morphological parameters. The testes of dogs were located within the scrotum and appeared oval in shape and reddish white in colour. The long axis of testis was placed dorso-caudal to the long axis of the body. The epididymis was attached to the dorso-lateral surface of the testis. Significant difference was noticed in the weight, length, circumference and the volume of the testes among dogs of prepubertal and post pubertal groups.